Guaranteeing Human Rights in Wartime: Directions for Modernization - Mykolaiets, Anatolii; Pavlichenko , Iryna; Kozakevych , Olesia; Koban, Olha; Puzyrna, Nataliia (NAJAHA, 2025)
This study aims to conduct an in-depth analysis of national and international aspects of human rights protection in wartime. The article updates the protection of human rights within the framework of the modern concept of comprehensive formation of effective counteraction to external and internal threats. The study examines the main functions of state bodies in ensuring the safety of the civilian population during martial law. The article examines the effectiveness of modern methods of regulating the human rights protection system, based on a risk-oriented approach to minimizing the consequences of wartime, identifying threats and preventing risks. It is substantiated that the priority in the implementation of national security should be the protection of geopolitical interests from the point of view of state and territorial integrity, protecting the independence of the state, guaranteeing high-quality and safe living conditions for citizens, as well as protecting their rights. An extensive analysis is conducted potential of existing international legal institutions regarding guarantees of protection. The article emphasizes the need to develop and implement international legal norms that guarantee the rigidity of the sanctions policy against the aggressor. The article proves that reliable protection of human rights requires ensuring the appropriate social prerequisites of unity and consensus between legal subjects at all levels. The originality of the study lies in the combination of theoretical and applied aspects of legal regulation and the provision of policy-oriented recommendations for legislators and international institutions. The results obtained can be used to develop a universal legal mechanism that will protect human rights in crisis geopolitical conditions . The conclusions come from case studies and primary legal analysis . A limitation of the study is the lack of practical cases of the implementation of new norms, which requires further empirical study of their implementation in different legal systems.